Regulatory Actions of LH and Follicle-Stimulating Hormone on Breast Cancer Cells and Mammary Tumors in Rats - Sanchez, Angel Matias; Flamini, Marina Ines; Zullino, Sara; Russo, Eleonora; Giannini, Andrea; Mannella, Paolo; Naccarato, Antonio Giuseppe; Genazzani, Andrea Riccardo; Simoncini, Tommaso (Frontiers in Endocrinology, 2018)
Gonadotrophins are mainly known to influence the body through the formation of gonadal steroids. However, receptors for luteinizing hormone (LHR) and follicular-stimulating hormone (FSHR) are present in a set of extra-gonadal tissues in humans and animals, but their functional relevance is uncertain. In this article we present experimental evidence that, in T-47D breast cancer cells, FSH and LH alter the expression of genes involved in adhesion, motility and invasion through the activation of their receptors. Using miniarray technology we also found that LH influences the expression of a broad set of genes involved in cancer biology in T-47D cells. Interestingly, the regulatory actions of FSH and LH depend on the modality of exposure, with significant differences between pre-pubertal-like vs. post-menopausal-like amounts of gonadotrophins, but not after intermittent administration, representative of fertile life. We also studied the modulation of the circulating levels of gonadotrophins in an in vivo rat model of breast cancer progression and observed a direct correlation with the extent of cancer growth. These results support the hypothesis that gonadotrophins may have direct effects on extra-gonadal tissues. They also highlight that gonadotrophins could potentially contribute to breast cancer progression, particularly in post-menopausal women who typically have higher gonadotrophin levels. This research may ultimately lead to testing the use of gonadotrophin-modulating drugs in breast cancer patients.